Reconceptualising translation in agricultural innovation: A co-translation approach to bring research knowledge and practice closer together. (January 2018) - Ingram, Julie; Dwyer, Janet; Gaskell, Peter; Mills, Jane; Wolf, Pieter de
Highlights: A reorientation of how the concept of translation is understood, theorised and operationalised in agriculture is presented. In this interactive methodology scientists and stakeholders identify innovation issues and solutions using a Dynamic Research Agenda. Constituent translation processes identified including: identification, articulation, retrieval, evaluation and synthesis. A concept of co-translation is developed to describe interactive and collaborative translation. Results lead to a rethinking of how translation is operationalised and the new mind-sets and skills required. Abstract: Scientific research continues to play a significant role in meeting the multiple innovation challenges in agriculture. If this role is to be fulfilled, provision needs to be made for effective translation of research outputs, where translation is understood to be the process whereby science becomes part of useful knowledge for decision making. There is increasing interest in enhancing translation in the European agricultural innovation, research and policy context, and specifically in making it a more collaborative process. This new attention calls for a reorientation of how the concept is understood, theorised and operationalised. This paper considers these needs and specifically asks how can interactive innovation approaches be integrated with science-driven approaches to enhance translation; and how can this help to reveal the constituent translation processes? An interactive stakeholder methodology is described drawing on three agricultural case studies examined in the xx project which aims to make translation of existing bodies of scientific knowledge more effective. Analysis to date shows how this interactive methodology enables a communicative and reciprocal set of translation processes to evolve which comprise: identification, prioritisation, articulation, searching, retrieval, extraction and synthesis, and evaluation of innovation issues and solutions. These insights allow us to move beyond an understanding of translation as science- or innovation-driven to envisaging co-translation, where multiple processes interact in a fluid middle-ground, and where the actors involved develop the capacity to jointly analyse innovation issues and solutions. From the perspective of the EU's policy ambitions to stimulate collaborative translation, operationalising translation needs re-thinking with respect to requirements for new mind-sets and skills, and in particular for committed and well-resourced intermediaries who can foster these multi-actors approaches.